Satu Frekuensi: Proses Sosial Ikatan Pelajar Muhammadiyah Yogyakarta - Sujibto, BJ.; Himmah, Izzatul (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
The social dynamics occurring within an organization can reflect many things such as balance, integration, conflict, and even the pattern and form of the organization itself. This article discusses the social processes and interactions that emerge in the student organization of the Muhammadiyah Student Association (IPM) of the Special Region of Yogyakarta in dealing with internal and external challenges and dynamics to build balance. These things are important as a learning process for students and to integrate mutual support among students and its member. Using a qualitative approach, this article researched the subject of the IPM at the Regional level with informants consisting of administrators. The article found two important things related to the pattern and form of social processes carried out by internal actors of the organization, such as (1) the role of actors who can understand the internal and external situations of the organization so that they can understand the dynamics of the organization; and (2) the intensity of communication and meetings is a fantastic way to maintain the internal IPM’s system so that it can be maintained to solve challenges and problems within internal organization. These two things are strengthened by the process of adaptation and integration that are approached formally and informally in the social process in IPM.